Developing ICC within the Activity Theory - Siek-Piskozub, Teresa (Glottodidactica, 2017)
The major goal of the article is to introduce the Activity Theory as a framework for developing intercultural communicative competence (ICC) of prospective foreign language teachers with the example of students from the Faculty of English (FE) at Adam Mickiewicz University in Poznań, Poland. I will refer to the concept of ICC resulting from the evolution of the concept of language competence in which social and cultural components have become more prominent, and for which the reference to the mythical.